Continued Fractions of Square Roots of Natural Numbers - L'ubomíra Balková; Aranka Hrušková (Acta Polytechnica, 2013)
In this paper, we will first summarize known results concerning continued fractions. Then we will limit our consideration to continued fractions of quadratic numbers. The second author describes periods and sometimes the precise form of continued fractions of ?N, where N is a natural number. In cases where we have been able to find such results in the literature, we recall the original authors, however many results seem to be new.